ANALISIS BEBAN KERJA PADA DIVISI PENGELOLAAN SUMBER DAYA MANUSIA DI PT X - Nasywa Eka Anindya; Darma Rika Swaramarinda; Suherdi (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the workload of employees in the Human Resources Management Division at PT X, covering workload conditions, factors contributing to the workload, and the impacts experienced by employees. The study employs a qualitative descriptive method to obtain an in-depth understanding of the workload conditions experienced by employees. Data collection was conducted through observation, in-depth interviews, and documentation, while the data analysis process involved data reduction, data presentation, and drawing conclusions. The results of the study indicate that employees’ workloads are high and do not align with their work capacity. Employees must complete routine tasks and periodic tasks simultaneously while meeting high demands for precision and speed. Regular working hours are deemed insufficient to complete all tasks, leading to frequent overtime. The high workload is influenced by limited staff numbers, time pressure, the complexity of interdepartmental coordination, technical constraints in operational systems, and the introduction of new tasks lacking clear guidelines. These conditions have physical and mental impacts on employees, such as fatigue, stress, and increased work pressure. Furthermore, the high workload also affects employee performance, as evidenced by decreased concentration and attention to detail, thereby increasing the likelihood of work errors. The results of this study indicate that workload is influenced not only by the volume of work but also by work systems, coordination mechanisms, and organizational policies that do not yet fully support employee work effectiveness.